Oxidation resistance of SiC ceramics prepared by different proceessing routes. Issue 15 (November 2016) - Kovalčíková, Alexandra; Sedláček, Jaroslav; Lenčéš, Zoltán; Bystrický, Roman; Dusza, Ján; Šajgalík, Pavol
Abstract: The oxidation behaviour at 1350–1450 °C/0–204 h of SiC ceramics was investigated as a function of the processing route. SiC ceramics were prepared by rapid hot-pressing of the granulated SiC powder without any oxide sintering additives. This method allows decreasing the sintering temperature around 200 °C than that conventionally used. Additive free rapid hot pressed SiC show better oxidation resistance compared to hot pressed liquid phase sintered SiC (the parabolic oxidation rates are about three orders of magnitudes lower). This new way prepared SiC ceramics show an interesting combination of properties like high Vickers hardness of 27.4 GPa, good fracture toughness of 3.42 MPa m 1/2, together with excellent oxidation resistance (4.91 × 10 −5 mg 2 /cm 4 h at 1450 °C).